STUDI EMPIRIS DEPRESIASI NILAI TUKAR RIIL PADA REZIM NILAI TUKAR MENGAMBANG BEBAS DI INDONESIA - Hartarto, Romi Bhakti (Jurnal Ekonomi & Studi Pembangunan, 2014)
Abstract: This study aims to analyze the relationship of real exchange rate depreciation with trade balance and national output as economic indicators in floating exchange rate regime. This study also observes whether J-curve phenomenon exists in Indonesia or not. This study employs quarterly data from year 2000:1 to 2010:4 as representation of floating exchange rate regime. Vector Error Correction Model is applied as an analytical tool by emphasizing on impulse response function to find out the response of one variable as caused by any shock from other variables in the model and variance decomposition to trace the relative contribution of one variable toward the variability of other variables in the model. This study demonstrates that real exchange rate depreciation contributes positively toward trade balance in longer time horizon. Nevertheless, national output does not respond positively toward real exchange rate depreciation. Another empirical finding suggests that there is no strong evidence of J-Curve phenomenon during free floating exchange rate regime in Indonesia. Â Abstrak: Tujuan studi ini ialah untuk menganalisis respon yang diterima oleh neraca perdagangan dan output nasional akibat depresiasi nilai tukar riil selama rezim nilai tukar mengambang bebas. Studi ini juga mencaritahu ada tidaknya fenomena kurva-J di Indonesia. Ada pun basis data yang digunakan pada studi ini ialah kuartalan dengan data observasi pada tahun 2000:1 hingga 2010:4 sebagai representasi periode rezim nilai tukar mengambang bebas.Studi ini menggunakan alat analisis Vector Error Correction Model yang lebih ditekankan pada fungsi impulse response untuk mengetahui respon yang diterima oleh suatu variabel akibat gejolak variabel lain dalam model dan dekomposisi varian untuk mengetahui kontribusi suatu variabel terhadap variabilitas variabel lain dalam model.Hasil dari studi ini menunjukkan bahwa depresiasi nilai tukar riil berhubungan positif dengan neraca perdaÂgangan dalam horizon waktu yang lebih panjang. Sementara itu, depresiasi nilai tukar riil justru berhubungan negatif dengan output nasional. Temuan lainstudi ini adalah tidak adanya bukti kuat yang menunjukkan fenomena kurva-J di Indonesia selama rezim nilai tukar mengambang bebas.Â